PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MEDIA PAPAN PINTAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA DI KELAS IV SD HARAPAN BARU MEDAN - Maria Gresia Agustina; Dyan Wulan Sari HS; Juliana; Ester Julinda Simarmata; Paska Sriulina Tarigan; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the problem-based learning model using smart boards on student learning outcomes in mathematics for fourth-grade students at Harapan Baru Elementary School in Medan in the 2024/2025 academic year. The research method used is an experimental method with a quantitative research design. To obtain the necessary data, a test instrument consisting of 25 questions was used. The sample size consisted of 30 students selected using purposive sampling. To assess students' initial abilities, the researcher conducted a pretest, yielding an average score of 55.2. The posttest results showed an improvement from the previous pretest, with students achieving an average score of 82.27. It can be said that the level of success in students' critical thinking skills has increased, as evidenced by the results of the correlation coefficient test, which yielded a result of rhitung ≥ rtabel with a result of 0.754 ≥ 0.361. Furthermore, the hypothesis testing compared the value of thitung ≥ ttabel with a result of 6.074 ≥ 2.042. With these results, Ha was accepted and Ho was rejected. Through the t-test, it can be concluded that there is an effect of the problem-based learning model using smart boards on student learning outcomes.